PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP INTEGRITAS INFORMASI LAPORANKEUANGAN DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL INTERVENING - Haniyah Mulia Diati, - (2020)
This research is using quantitative study aimed to see whether there are influence of institutional ownership and competence of audit committees on the integrity of financial statement information through financial distress as an intervening variable. A sample of 95 manufacturing companies listed on the Indonesia Listed Exchange in the 2016-2018 period were using purposive sampling. The analysis technique used is path analysis using SmartPLS 3.2.8 software with a significance level of 5%. The contribution of this research is to use the financial distress factor as an intervening variable and the research method uses the Structural Equation Model (SEM). The result of the tests indicate that (1) Institutional ownership has a significant effect on the integrity of financial statement information (2) The competence of audit committee has a significant effect on the integrity of the financial statement information (3) Institutional ownership has a no significant effect on financial distress (4) The competence of audit committee has no significant effect on financial distress (5) Financial distress has a significant effect on the integrity of financial statement information (6) Institutional ownership has no significant effect on the integrity of financial statement information through financial distress (7) The competence of audit committee has no significant effect on the integrity of financial statement information through financial distress.